Pengembangan Video Edukasi “Jejak Jena Joni” Sebagai Media Pembelajaran Keberagaman Budaya Kelas IV Sekolah Dasar - Dela Perdayanti; Tita Tanjung Sari; Kadarisman Kadarisman (LPPM Press, 2022)
This study aims to: (1) describe the development of Jena Joni's Footsteps Educational Video as a Learning Media for Cultural Diversity for Grade IV Elementary School (2) to determine student responses to the development of Jena Joni's Footsteps Educational Video as a Learning Media for Cultural Diversity for Grade IV Elementary School. The method in this research is the Borg and Gall model development method which has been modified by Sugiono (2014). The results showed that: (1) the development in this study was declared feasible to be used as a learning medium, this was based on the results of the validation of media and material design with a percentage of 95%, 94%, respectively, with the criteria of